KORELASI KEPRIBADIAN DOSEN DENGAN MOTIVASI BELAJAR MAHASISWA DALAM PBM MATA KULIAH MEMBACA (READING) DI JURUSAN BAHASA DAN SASTRA INGGRIS UNIVERSITAS NEGERI PADANG - Leni Marlina; Fitrawati Fitrawati; Delvi Wahyudi (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2018)
This paper discusses the results of research on empirical descriptions relating to three points in the Reading (Reading) course in the English Department of Padang State University. The three things studied consisted of (1) the personality of the lecturer in the teaching and learning process of the Reading program based on the student's point of view; (2) student learning motivation in the process of reading learning; and (3) the relationship between lecturer personality and student motivation in the process of reading learning. This research uses a descriptive method. The study population was all students who had studied four types of reading (Reading) courses at the UNP Padang English Department in 2015. The courses were Reading I, Reading II, Reading III, and Advanced Reading. This study uses total sampling. There are three findings from this study. First, the personality of the lecturer in the teaching and learning process of Reading courses based on the students' point of view is in a good category. Second, the motivation of students in the learning process of Reading subjects is also included in the good category. Finally, this study shows that there is no strong relationship between lecturer personality and student motivation in the learning process of reading courses in the UNP Padang English Department.